Karo Traditional Business Development - Yayuk Yuliana; Diana Sopha (Yayasan Ilomata, 2020)
In the village, Batu Jong-Jong Village, Bahorok District the land is very fertile. Lush plants that can be used as a mixture of traditional medicines. Housewives with a hereditary recipe to produce herbs derived from plants that become traditional business ingredients Karo. The purpose of this research is to find out alternative strategies and priority strategies that can be used as an effort to develop karo traditional ingredients in Batu Jong-Jong Village. Research methods with a qualitative descriptive approach. Data collection through interviews, observations, discussions. Interviews were conducted with the owners of the traditional herbs Karo business in the stone frog hamlet and also a questionnaire with forestry counselors and village heads. The results of the study, based on the results of the calculation of the IFE (Internal Factor Evalution) matrix, found that the total score was 3.15. While the results of calculations on the EFE (External Factor Evalution) matrix table, obtained a total weighted score of 2.87. The conclusion is that the traditional herb business in Karo is of moderate value because the score weight is above 2.50. So that the right strategy is market penetration and product development strategies.